Techno-environmental assessment of marine gas turbines for the propulsion of merchant ships - Bonet, Mathias Usman (Cranfield University, 2011)
This research study seeks to evaluate the techno-economic and environmental implications of a variety of aero-derivative marine gas turbine cycles that have been modelled for the propulsion of different types of merchant ships. It involves the installation and operation of gas turbine propulsion systems in different marine environmental conditions and aims to evaluate the effect of the aerodynamic and hydrodynamic variations expected to be encountered by these ships when they navigate across different climates and oceans along selected fixed trade routes. A combination of simulation tools developed in Cranfield University at the Department of Power and Propulsion including the validated gas turbine modelling and simulation code called “Turbomatch” and the “APPEM” simulation code for the analysis and Prediction of exhaust pollutants have been used along with the ongoing development of an integrated marine gas turbine propulsion system simulation platform known as “Poseidon”. It is the main objective of this research to upgrade the competence level of “Poseidon” so as to facilitate the conduct of a variety of longer and more complex oceangoing voyage scenarios through the introduction of an ambient temperature variation numerical module. Expanding the existing code has facilitated the prediction of the effect of varying aerodynamic and hydrodynamic conditions that may be encountered by gas turbine propulsion systems when such ships navigate through unstable ocean environments along their fixed trade routes at sea. The consequences of operating the marine gas turbines under ideal weather conditions has been investigated and compared with a wide range of severe operating scenarios under unstable weather and sea conditions in combination with hull fouling has been assessed. The techno-economic and environmental benefits of intercooling/exhaust waste heat recuperation of the ICR model have been predicted through the evaluation of different ship propulsion performance parameters in a variety of voyage analysis leading to the prediction of fuel consumption quantities, emission of NOx, CO2, CO and UHCs and the estimation of the HPT blade life as well. The different gas turbine cycle configurations of the research were found to respond differently when operated under various environmental profiles of the ship’s trade route and the number of units for each model required to meet the power plant capacity in each scenario and for each ship was assessed. The study therefore adds to the understanding of the operating costs and asset management of marine gas turbine propulsion systems of any ocean carrier and in addition it reveals the economic potentials of using BOG as the main fuel for firing gas turbine propulsion plants of LNG Carriers.
Keywords: Performance; Emissions; Weather; Sea states; Voyage; Hull Fouling; Transit time; BOG